In-silico Studies of Epoxy-Thioxanthone Derivatives as Potential Tyrosine Kinase Inhibitor Using Molecular Docking, Molecular Dynamics Simulations, MM-PBSA and ADMET - Hermawan, Faris (2024)
Protein tyrosine kinases play a role in the cell signaling pathways involving cell growth, differentiation, apoptosis, and metabolism of cancer cells. Because of that, the molecular docking, molecular dynamics, MM-PBSA, and prediction ADMET properties were conducted to evaluate the inhibition activity of epoxy-thioxanthones against platelet-derived growth factors receptor (PDGFR) and epidermal growth factor receptor (EGFR) proteins. A series of ten thioxanthone compounds bearing hydroxy, epoxy, chloro, and bromo substituents have been designed and evaluated. The docking results showed that the epoxy-thioxanthones ( A-J ) have binding energy from -7.12 to -9.81 and -7.24 to -8.06 kcal/mol against those proteins, respectively. Compared with the native ligands, all epoxy-thioxanthones gave stronger binding energy (-7.24 to -8.06 kcal/mol) with the active site of EGFR than the erlotinib (-7.05 kcal/mol), which is remarkable. This result is also in line with the molecular dynamics results. The calculation of binding energy MM-PBSA that compounds D , E , I , and J had comparable EGFR protein stability to erlotinib. The binding energy of those compounds (-19.29 to -29.35 kcal/mol) had lower than erlotinib (-8.25 kcal/mol). Furthermore, in physicochemical properties prediction, those compounds fulfill Lipinski’s rule parameters and the minimum standard parameters in ADMET properties.